Nancy Drew mystery stories : the secret of shadow ranch - Keene, Carolyn (New York : Grosset & Dunlap, 2015)
Strange things happen when Nancy investigates threats against her father and an old house said to be haunted.
5-8
English.
Keywords: Drew, Nancy (Fictitious character) -- Juvenile fiction; Drew, Nancy (Fictitious character) -- Fiction; Mystery and detective stories; Drew, Nancy (Fictional character) -- Fiction; Mystery fiction; Mystery fiction